Association Between Titration Method and Outcomes of First Night Satisfaction and CPAP Compliance - Sökücü, Sinem Nedime (Noro Psikiyatr Ars, 2018)
INTRODUCTION: The gold standard therapy for obstructive sleep apnoea syndrome (OSAS) is continuous positive airway pressure (CPAP). Our study evaluated the relationship between first night satisfaction and CPAP compliance, and the effect of using the titration method in this relationship. METHODS: Between January 2012 and December 2012, 40 patients with the diagnosis of OSAS and without comorbidities, who had undergone CPAP titration, were included. Of these, 20 patients had undergone manual titration (MT) with polysomnography, whereas 20 patients had undergone auto-adjusted CPAP (APAP) titration. Questionnaires were administered during the morning of the titration night. The first-year adherence to treatment and patient compliance were evaluated. RESULTS: Forty patients were randomised in two groups; 35 patients who could procure the CPAP and were available at the end of the first year completed the study. From the 35 patients, 20 (6 males; 40%) were in the MT group while 15 (6 males; 30%) were in the APAP group. No significant difference was detected between the mean titration pressure levels obtained with the MT or APAP group. There was no difference in terms of responses to the questions on the questionnaire between the two groups. At the first-year evaluation, no significant difference was detected between the groups. CONCLUSIONS: The titration method used to detect CPAP pressure, MT, or APAP does not affect patient satisfaction on the day following the titration night, and does not affect first-year compliance.